PENGARUH PENGALAMAN PELANGGAN DAN KEPERCAYAAN TERHADAP NIAT BELI ULANG SECARA ONLINE MELALUI KEPUASAN PELANGGAN (Studi Pada Situs Online Berrybenka.com) - Yolandari, Ni Luh Dian; Kusumadewi, Ni Made Wulandari (E-Jurnal Manajemen, 2018)
The purpose of this study to determine the effect of customer experience, trust, customer satisfaction and re-purchase intention at online shopping site Berrybenka.com. The study was conducted in Denpasar City, using sample size of 112 people. Data were obtained by distributing questionnaires measured by Likert Scale. Data analysis techniques used in the form of classical assumption test, path analysis and equipped with test sobel. The results of this study indicate that customer experience and trust have a positive and significant effect on customer satisfaction. Customer experience and trust have a positive and significant impact on repurchase intentions. Customer satisfaction is able to positively mediate and significantly impact the customer's experience on repurchase intentions. Customer satisfaction is able to positively and positively mediate the effect of trust on repurchase intentions. Berrybenka.com is expected to maintain and even increase customer satisfaction so that it will impact on the intention to buy back. With the intention of buy back can affect the quality of online shopping site Berrybenka.com. Keywords : customers experience, trust, customer satisfaction, and repurchase intention